ANALISIS MEDIASI GREEN TRUST PADA PURCHASE INTENTION PRODUK GREEN - Suprapto, Dea Yulyana; Efendi, Efendi (Master of Management Diponegoro University, 2017)
In today's era, consumer's attitude in choosing and using the product start to change. Consumers begin to have awareness and concern about the impact of consumption on the environment. Many consumers are now choosing green products because of better value and functionality for consumers and the environment. This study aims to analyze the effect of green perceived value and green perceived risk on green purchase intention with green trust as mediation. Data was obtained by distributing questionnaires to consumers who visit Electronics City Pondok Indah Mall. Sampling technique applied in this research is systematic random sampling. Data was analyzed using SEM (Structural Equation Modeling).